What Do Pupils’ Parents Think About School Segregation? - Rusnáková, Jurina; Rusnák, Július; Rosinský, Rastislav; Rochovská, Alena; Odrášková, Barbora (Porównania, 2018)
In the Slovak practice, separated (segregated) education is rather common at primary schools as well as in preschool facilities. Despite the repeated warnings by the EU, the schools near Roma communities use such separation. They argue that this education supports an “individual approach” to Roma pupils because “Roma” classes are smaller, and an important argument is the pressure from non-Roma parents. According to schools, they prefer ethnically homogenous classes and they choose schools for their children based on this (they are not interested in schools with a higher proportion of Roma pupils). The paper states the opinions of parents of Roma and non-Roma children on separated education which were obtained in the interviews and focus groups in the study focused on analysis of inclusive education projects and programmes.